Forming Approaches to Strategic Management and Development of Tourism and Hospitality Industry in the Regions - KONOVALOVA, Elena Evgenievna; YUDINA, Elena Vladimirovna; BUSHUEVA, Irina Viktorovna; UHINA, Tatiana Viktorovna; LEBEDEV, Kostyantyn Anatol'evich (Journal of Environmental Management and Tourism; Vol 9 No 2 (2018): JEMT Volume IX Issue 2(26) Spring 2018DO - 10.14505//jemt.v9.2(26).03, 2018)
The paper refers with the development of approaches to strategic management and development of the tourism and hospitality industry in the regions. The authors justified the creation of a strategy selection model that would take into account the possible strategic positions in organization of the tourism and hospitality industry, as well as unexpected strategic changes in the external business environment that might occur on its path. The model is based on the system of strategy selection and classification of unexpected strategic changes in the external business environment. It is proved that the application of the strategic management concept in tourism and hospitality industry is possible only taking into account the specifics of the organization’s activities, interests of service consumers, existing competitive conditions, and the sustainable development principles. It is revealed that there is a need in a holistic management system that would meet current and future requirements of the dynamic development of the tourism and hospitality industry, and can be implemented at different levels including regional level.